A novel 3-D chaotic system with line equilibrium: dynamical analysis, coexisting attractors, offset boosting control and circuit design - Mustafa, M.; Sambas, A.; Vaidyanathan, S.; Zhang, S.; Mujiarto, .; Sukono, .; Subiyanto, . (2019)
A 3-D new chaotic system with five nonlinearities is proposed in this paper. A novel feature of our chaotic system is that there is no linear term in it. We also show that the chaotic system consists of equilibrium points on the z-axis (line equilibrium) as well as two equilibrium points on the (x, y)-plane. The dynamical properties of the new chaotic system are described in terms of phase portraits, bifurcation diagram, Lyapunov exponents, coexisting attractors, coexisting bifurcation and offset boosting control. Finally, an electronic circuit realization of the new chaotic system is presented in detail to confirm the feasibility of the theoretical chaotic model.